Preauricular sinus: a clinicopathological study - Gupta, Richa; Agrawal, Anil; Poorey, V. K. (International Journal of Research in Medical Sciences, 2017)
Background: Preauricular sinuses are common congenital malformations. In most instances the diagnosis and management of condition is straightforward. Methods: The present study was done on 26 patients of preauricular sinus who presented to the Department of ENT, S.S. Medical College & G.M. Hospital, Rewa from August 2012 to July 2013 prospectively. Results: Males and females were equally affected. Most patients i.e. 11 belong to 11-20 year age group with age ranging from 4 year to 60 years. Two cases had genetic history and one case was found to be associated with chronic suppurative otitis media (CSOM). Conclusions: The patients in whom a preauricular sinus is identified, the associated congenital anomalies and family history should be sought. Early identification and spreading of awareness should be done to avoid the complication of recurrent abscess in preauricular region.